2019
DOI: 10.12669/pjms.36.1.706
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Sulfate in combination with Nifedipine in the treatment of Pregnancy-Induced Hypertension

Abstract: Objective: To investigate the effect of magnesium sulfate combined with nifedipine in the treatment of pregnancy-induced hypertension syndrome (PIHS). Methods: Total 118 pregnant women with PIHS who were admitted to our hospital from April 2017 to June 2018 were randomly divided into control group (59 cases) and observation group (59 cases). The observation group was treated by magnesium sulfate in combination with nifedipine, while the control group was treated by magnesium sulfate. The therapeutic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Magnesium sulfate has the antagonistic effect of Ca 2+ and is mainly used for anticonvulsion. It can reduce blood pressure by causing vascular dilation, further improve human microcirculation, and can be used for the treatment of hypertensive crisis [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium sulfate has the antagonistic effect of Ca 2+ and is mainly used for anticonvulsion. It can reduce blood pressure by causing vascular dilation, further improve human microcirculation, and can be used for the treatment of hypertensive crisis [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ma Xiaolian et al discussed the role of Nemothoracoplasty combined with magnesium sulfate injection in the clinical treatment of hypertensive disorders during pregnancy [29]. The results indicated that the overall effective rate in the combination group was 95.74%, significantly higher than the 82.22% in the magnesium sulfate group (P<0.05).…”
Section: Combined Use Of Multiple Drugsmentioning
confidence: 99%
“…1,2 Not only does it contribute to the latter, but is also associated with prolonged chronic hypertension, renal failure, or neurological disorders, which may, in turn, contribute to most pregnancy-related health complications. [3][4][5] Research has established maternal mortality and morbidity as the worse health issue on a universal scale. Global estimations demonstrate that 287 000 women died from a maternal cause during 2020, which equates to about 800 maternal deaths per day.…”
Section: Introductionmentioning
confidence: 99%